PENINGKATAN EFISIENSI PEMUPUKAN FOSFOR PADA ULTISOL DENGAN MENGGUNAKAN ABU TERBANG BATUBARA - F Fahrunsyah; M Mulyadi; Agus Sarjono; Surya Darma (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2021)
Ultisol is one type of soil that has a very wide distribution in Indonesia, but the use of this soil faces many obstacles. The main problem in ultisol utilization is the low availability of phosphorus (P) and the low absorption efficiency. Coal fly ash (CFA) is a material that can overcome these problems. The objective of this study was to examine the effect of Application CFA on several soil chemical properties (pH, exchangeable Al, exchangeable Ca and available P), plant growth, yield, and absorption efficiency of P fertilizer. This study used a completely randomized factorial design consisting of two factors. The first factor was CFA that consisted of three levels of treatment, namely: A0 = 0 t ha-1 or without CFA, A1 = 40 t CFA ha-1, A2 = 80 t CFA ha-1. The second factor was P fertilizer that consisted of four levels of treatment, namely: P0 = 0 kg ha-1, P1 = 30 kg P ha-1, P2 = 60 kg P ha-1 and P3 = 90 kg P ha-1. The results of the study showed that the application of 80 t CFA ha-1 increased the pH by 13.41%, reduced exchangeable Al by 59.53% and increased exchangeable by Ca 192.66% compared to control. The combination 80 t CFA ha-1 and 90 kg P ha-1 increased available P by 986.79% compared to control. The application of 80 t CFA ha-1 resulted in the highest total plant dry weight and total P uptake. The treatment resulted in total plant dry weight of 172.96 g and total P uptake of 187.62 mg plant-1, increased 62.39% and 100.21% respectively compared to the control. The application of 90 kg P fertilizer ha-1 resulted in the highest total dry weight of maize, and total P uptake, namely 167.49 g and 174.39 mg plant-1, respectively, which means that the total plant dry weight increased by 51.00% and the total uptake P increased 69.79% compared to control. The highest seed dry weight was obtained in the combination of 80 t CFA ha-1 and 90 kg P ha-1, namely 39.33 g, an increase of 715.53% compared to the control. The combination of 40 t CFA ha-1 and 30 kg P ha-1 resulted in the highest absorption efficiency of P fertilizer, namely 30.43%. This means that in this treatment, maize can absorb 30.43% of the applied P fertilizer.